Penerapan Regresi Logistik Biner Terhadap Faktor-Faktor yang Memengaruhi Pemanfaatan Jaminan Kesehatan Pasien Rawat Jalan di Provinsi Nusa Tenggara Barat Tahun 2020 - Ririn Riana HashunatilMar'ah; Yaya Setiadi (Politeknik Statistika STIS, 2022)
Health insurance has benefit for society because it doesn’t have to spend money. But, in reality health insurance not utilized well. Only 31,09 percentage of people using health insurance in 2020 in West Nusa Tenggara Province. This number is low if we considering there are 61,69 percentage of Nusa Tenggara Barat people have health insurance. The purpose of this research is to know general description also to analyse factors that influence the utilization of health insurance in Nusa Tenggara Barat province 2020. Data that be using in this research is raw data from Susenas KOR Maret 2020 with analytical method that would be using is binary logistic regression. The result are residence,age,job and education significance with the utilization of health insurance in Nusa Tenggara Barat province 2020. As for gender doesn’t significance with the utilization of health insurance in Nusa Tenggara Barat province 2020.